1992
DOI: 10.1111/j.1432-1033.1992.tb17016.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of yeast phosphoglycerate kinase modified by mutagenesis at residue 21

Abstract: Site-directed mutagenesis has been used to produce mutant forms of yeast phosphoglycerate kinase in which the conserved active-site residue, Arg21, has been replaced by a methionine or a lysine. Kinetic results obtained using these mutant enzymes show that their K,,, for both 3-phospho-D-glycerate and ATP are significantly different from those recorded for the wild-type enzyme. The V,,, for the lysine mutant is reduced by a factor of two from that of the wild-type enzyme whereas the V,,, for the methionine mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…3-PG is bound nearly in the same way in all PGK crystal structures. In agreement, site-directed mutagenesis studies (24)(25)(26)(38)(39)(40)(41)(42)(43) have confirmed the importance of the basic residues at the inner surface of the N-domain in binding of this substrate. The extended basic patch can also bind various anions, as shown by various techniques (42,(44)(45)(46)(47).…”
supporting
confidence: 71%
See 2 more Smart Citations
“…3-PG is bound nearly in the same way in all PGK crystal structures. In agreement, site-directed mutagenesis studies (24)(25)(26)(38)(39)(40)(41)(42)(43) have confirmed the importance of the basic residues at the inner surface of the N-domain in binding of this substrate. The extended basic patch can also bind various anions, as shown by various techniques (42,(44)(45)(46)(47).…”
supporting
confidence: 71%
“…These activation phenomena are peculiar regulatory behaviors of PGK, the molecular basis of which is still not completely understood. The anion activation is diminished or completely abolished in the case of some basic patch mutants (39,41,43), but the data have not yet provided a satisfactory explanation about the location of the activating site and the molecular mechanism of activation. A hypothesis was put forward about formation of the activating anionic site only upon domain closure (50).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The apparent anomalous increase in activity of the Pro204Phe mutant may be due to restructuring of the enzyme in sulphate. It is accepted that the ‘basic patch’ is an extended anion binding site containing both the triose binding site and the anion activatory site [30, 31]. The higher affinity of the activatory site allows anions to bind at low anionic concentrations, whilst anions only bind the inhibitory site at higher anionic concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Watson et al, 1982) and by NMR [reviewed in Joao and Williams (1993)]. PGK is a single polypeptide chain of about 45 kDa, and the probing of the roles of several amino acid residues in its catalytic function has been carried out by site-directed mutagenesis [e.g., Ballery et al (1990), Sherman et al (1992), andWalker et al (1992); reviewed in Joao and Williams (1993)]. From these structural studies the binding of either substrate induces a conformational change, that with PG being the larger.…”
mentioning
confidence: 99%